TMOD-36. THE DEVELOPMENT OF A NOVEL MOUSE MODEL TO STUDY THE ROLE OF HISTONE MUTATIONS AND MODIFICATIONS IN PEDIATRIC HIGH-GRADE GLIOMA. (9th November 2020) - Grigore, Florina; Day, Charles; Hanson, Nicholas; Langfald, Alyssa; Sarkaria, Jann; Daniels, David; Hinchcliffe, Edward; Robinson, James
Abstract: Pediatric glioblastoma and diffuse intrinsic pontine glioma are high-grade gliomas of children (pHGG) with a median overall survival of under 15 months and among the most lethal cancers. Mutations in histone H3.3 and H3.1 occur as an early event in pHGG. H3.3G34R/V-mutations occur in pHGG of cerebral hemispheres, and H3.3K27M mutations occur in midline pHGGs. Post-translational histone modifications (PTMs) serve to regulate gene expression by relaxing or compacting chromatin and by recruiting proteins, with subsequent silencing or activating effects. H3.3 Serine 31 (S31) shows reduced phosphorylation during mitosis in H3.3G34R/V and H3.3K27M mutant cell. Phosphorylation at S31 is restored in wildtype H3.3K27 CRISPR revertants. Serine to alanine (A) mutant H3.3 S31A are nonphosphorylatable in vitro . To study the influence of histone mutations and the role of altered PTM and including the loss of methylation and phosphorylation on tumorigenesis, we have developed an innovative model based on the RCAS/N-TVA mouse model. In this system, the expression of an oncogenic driver is linked to mutant histone expression using a self-cleaving peptide, and tumors develop following viral delivery to neural stem cells in newborn mice. This approach is necessary, as otherwise, clonal selection could prevent tumors from forming with mutations detrimental to growth. To establish the model, N-TVA mice were injected with RCAS H3.3K27M-P2A-PDGFB, RCAS H3.3G34R-P2A-PDGFB, or H3.3WT-P2A-PDGFB. The mean survival of mice injected with H3.3K27M and H3.3S31A was 81 and 68 days, respectively, and 100% of S31A mice developed HGG. In contrast, H3.3WT caused only low-grade tumors in 46% of the mice, and all mice survived until 100 days. In ongoing experiments with H3.3G34R, 23% of mice succumb to tumors by 80 days. These results provide mechanistic insights into the early establishment of pHGGs and established a new mouse model to study the role of histone mutation and PTMs in tumor development.